Role of fourth transmembrane domain and the second extracellular loop in structure-activity relationships in D1-like dopaminergic receptors - Ogden, Nancy (University of Ottawa (Canada), 2005)
The mammalian D1-like dopaminergic receptors are composed of two subtypes, D1R (or D1A) and D5R (or D1B), which belong to the large family of heptahelical G protein-coupled receptors (GPCRs). D1R and D5R receptors have been characterized pharmacologically via their ability to couple to Galphas and activate AC. Against the high overall amino acid sequence homology of the two D1-like dopaminergic receptors, the divergent primary structure of the extracellular loops, as well as discrete residues within the exofacial end of the transmembrane (TM) regions provide new targets for the assessment of structure-activity relationships represented by D1R and D5R. While residues within the second extracellular loop (EL2) of a number of GPCRs have been the subject of site-directed mutagenesis, a broader understanding of the structure-activity role of EL2 as a whole has yet to be formed. In the present study, chimeric proteins have been engineered to swap the EL2 of D1R and D5R receptors, both with and without the exchange of the divergent amino acid in the exofacial end of TM4. (Abstract shortened by UMI.)
Keywords: Health Sciences, Pharmacology.